Frequency, predictors and cardiovascular outcomes associated with transthoracic echocardiographic findings during acute ischaemic stroke hospitalisation. Issue 6 (13th June 2022) - Sharma, Richa; Silverman, Scott; Patel, Shaun; Schwamm, Lee H; Sanborn, Danita Yoerger
Abstract : Objective: To characterise the clinical utility of transthoracic echocardiography (TTE) at the time of acute ischaemic stroke (AIS). Background: The utility of obtaining a TTE during AIS hospitalisation is uncertain. Methods: We studied AIS hospitalisations at a single centre (2002–2016). TTE abnormalities were classified as findings associated with: high stroke risk (Category I), cardiac events (Category II) and of unclear significance (Category III). We performed logistic regressions to predict Category I, II and III abnormalities. The odds of 1 year recurrent stroke hospitalisation captured by ICD 9 and 10 codes as a function of Category I, II and III abnormalities were assessed. Improvement in predictive capacity for 1 year recurrent ischaemic stroke hospitalisation beyond stroke risk factors was evaluated by net reclassification improvement. Results: There were 5523 AIS hospitalisations. Nearly 81% of admission TTEs were abnormal (18.7% Category I, 32.7% Category II, 72.8% Category III). Older patients with coronary artery disease, atrial fibrillation, hypertension, diabetes, and patent intracranial and extracranial vessels were likely to have an abnormal TTE. Category I finding was associated with lower odds of 1-year recurrent stroke hospitalisation (OR 0.54, 95% CI 0.30 to 0.96). Category I data significantly improved the predictive value for 1-year recurrent ischaemic stroke hospitalisation beyond stroke risk factors (net reclassification improvement 0.1563, 95% CI 0.0465 to 0.2661). Conclusions: TTE abnormalities associated with stroke and cardiac event risk were commonly detected during AIS hospitalisation. Detection of Category I TTE findings reduced the risk of recurrent stroke, potentially due to neutralisation of the cardioembolic source by targeted therapy, indicating the clinical utility of TTE.